Validation of the “Interactive Breastfeeding Scale”: theoretical and empirical analysis - Primo,Cândida Caniçali (2020)
ABSTRACT Objective: To conduct a theoretical and empirical analysis of the Interactive Breastfeeding Scale. Method: A methodological study that followed the measurement method by Pasquali and was carried out in two stages: theoretical analysis with 40 nurses as content's judges and a pilot survey with 68 mothers of a maternity hospital of a university hospital in southeastern Brazil. Results: The evaluation with judges showed that the items of the scale are accurate on the theoretical concept, semantic adequation, and pertinence. From 58 items on the scale, 33 had a Content Validity Index greater than or equal to 0.80. The pilot survey allowed us to evaluate the items in the social and cultural context of the target population. In the end, the scale remained with 30 items. Conclusion and implication for the practice: The validation with the judges showed that the items of the Interactive Breastfeeding Scale are accurate to the theoretical concept regarding semantics and relevance and proved to be a reliable and valid instrument to evaluate the factors that interfere in mother-child interaction during breastfeeding.